At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Alright, let's solve these equations step by step.
### Equation 1: [tex]\(7x + 9 = 3 + 9x\)[/tex]
1. Isolate the variable terms on one side: Start by moving all terms involving [tex]\(x\)[/tex] to one side of the equation. We can subtract [tex]\(9x\)[/tex] from both sides:
[tex]\[ 7x + 9 - 9x = 3 \][/tex]
2. Simplify the equation: Combine like terms:
[tex]\[ 7x - 9x + 9 = 3 \implies -2x + 9 = 3 \][/tex]
3. Isolate [tex]\(x\)[/tex]: Move the constant term on the left side to the right side by subtracting 9 from both sides:
[tex]\[ -2x = 3 - 9 \implies -2x = -6 \][/tex]
4. Solve for [tex]\(x\)[/tex]: Divide both sides by [tex]\(-2\)[/tex]:
[tex]\[ x = \frac{-6}{-2} \implies x = 3 \][/tex]
So, the solution to the first equation is [tex]\(x = 3\)[/tex].
### Equation 2: [tex]\(x + 1 = 2x - 7\)[/tex]
1. Isolate the variable terms on one side: We start by moving all terms involving [tex]\(x\)[/tex] to one side of the equation. We can subtract [tex]\(x\)[/tex] from both sides:
[tex]\[ x + 1 - x = 2x - 7 - x \][/tex]
2. Simplify the equation: Combine like terms:
[tex]\[ 1 = x - 7 \][/tex]
3. Isolate [tex]\(x\)[/tex]: Move the constant term on the right side to the left side by adding 7 to both sides:
[tex]\[ 1 + 7 = x \implies x = 8 \][/tex]
So, the solution to the second equation is [tex]\(x = 8\)[/tex].
### Summary of Solutions
- For the equation [tex]\(7x + 9 = 3 + 9x\)[/tex], the solution is [tex]\(x = 3\)[/tex].
- For the equation [tex]\(x + 1 = 2x - 7\)[/tex], the solution is [tex]\(x = 8\)[/tex].
Thus, the solutions to the given equations are:
[tex]\[ x = 3 \quad \text{and} \quad x = 8 \][/tex]
### Equation 1: [tex]\(7x + 9 = 3 + 9x\)[/tex]
1. Isolate the variable terms on one side: Start by moving all terms involving [tex]\(x\)[/tex] to one side of the equation. We can subtract [tex]\(9x\)[/tex] from both sides:
[tex]\[ 7x + 9 - 9x = 3 \][/tex]
2. Simplify the equation: Combine like terms:
[tex]\[ 7x - 9x + 9 = 3 \implies -2x + 9 = 3 \][/tex]
3. Isolate [tex]\(x\)[/tex]: Move the constant term on the left side to the right side by subtracting 9 from both sides:
[tex]\[ -2x = 3 - 9 \implies -2x = -6 \][/tex]
4. Solve for [tex]\(x\)[/tex]: Divide both sides by [tex]\(-2\)[/tex]:
[tex]\[ x = \frac{-6}{-2} \implies x = 3 \][/tex]
So, the solution to the first equation is [tex]\(x = 3\)[/tex].
### Equation 2: [tex]\(x + 1 = 2x - 7\)[/tex]
1. Isolate the variable terms on one side: We start by moving all terms involving [tex]\(x\)[/tex] to one side of the equation. We can subtract [tex]\(x\)[/tex] from both sides:
[tex]\[ x + 1 - x = 2x - 7 - x \][/tex]
2. Simplify the equation: Combine like terms:
[tex]\[ 1 = x - 7 \][/tex]
3. Isolate [tex]\(x\)[/tex]: Move the constant term on the right side to the left side by adding 7 to both sides:
[tex]\[ 1 + 7 = x \implies x = 8 \][/tex]
So, the solution to the second equation is [tex]\(x = 8\)[/tex].
### Summary of Solutions
- For the equation [tex]\(7x + 9 = 3 + 9x\)[/tex], the solution is [tex]\(x = 3\)[/tex].
- For the equation [tex]\(x + 1 = 2x - 7\)[/tex], the solution is [tex]\(x = 8\)[/tex].
Thus, the solutions to the given equations are:
[tex]\[ x = 3 \quad \text{and} \quad x = 8 \][/tex]
We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.